Evaluation of the Phytochemical, Antioxidant and Antimicrobialproperties of Extracts from Chrysophyllum Albidum (African Star Apple) Leaf - O.O, Oguntoyinbo; R.B, Abdus-Salaam; W.A, Bello; B.O.T, Ifesan (Journal of Food Technology Research, 2015)
Phytochemical, antioxidant and antimicrobial properties of n-butanol, petroleum ether and ethanol extracts of the leaf of Chrysophyllumalbidum were investigated. Antioxidant activity was carried out using various tests which include; 2, 2-diphenyl-picrylhydrazyl (DPPH) scavenging activity, total antioxidant activity, ferric reducing antioxidant power (FRAP), total flavonoid content and the total phenolic content. The antimicrobial test was conducted on the following micro-organisms; Salmonella dysenteriae, Bacillus cereus, Salmonella typhi, Acinetobacter spp., Escherichia coli, Klebsiellapneumoniae, Penicillum spp., Aspergillusflavus, Fusariumverticoides, Aspergillus tamari and Aspergillusparasiticus using the agar well diffusion method. Results revealed that petroleum ether gave the highest extract yield (16.8%) while butanolic extract had the least yield (4.6%). At 250 µg/ml extract concentration, petroleum ether extract demonstrated the highest (73.57%) DPPH scavenging activity followed by ethanol extract (59.32%) while butanolic extract had the least scavenging activity of 32.02%, and these were significantly different (P<0.05). Total antioxidant activity (ascorbic acid equivalent) of C. albidum ranged from 42.33AAE in butanol extract to 50.6AAE in ethanol extract. Furthermore, ferric reducing antioxidant power (FRAP) of the leaf extracts revealed that at 250 µg/ml extract concentration, ethanol extract had the highest (0.39µmolFe(ii)/g) reduction potential, followed by petroleum ether extract (0.33µmolFe(ii)/g) and butanol extract (0.29 µmolFe(ii)/g). The total phenol content of the extracts ranged from 0.02µg/mlTAE–0.09µg/mlTAE at 1000µg/ml extract concentration. The total flavonoid content ranged from 0.47mg/gQE in petroleum ether extract to 12.74mg/gQE in butanol extract . The antimicrobial activities of the extracts of the leaf of C. albidum showed zone of inhibition ranging from 9.7mm to 31.0mm. The result showed that butanolic extract demonstrated a broad spectrum antimicrobial activity by inhibiting all the microorganisms tested while petroleum ether extract possessed no antimicrobial property. This result may be an indication that C. albidumleaf extracts could be used as an easily accessible source of natural antioxidant and antimicrobial agent.